Stability of Bacillus pumilus spore strips used for monitoring radiation sterilization. - Prince, H N (1976)
Dried Bacillus pumilus spore strips had a stable D-value of 0.17 to 0.18 Mrad after 1 year at 5 or 25 C, but resistance was lost at 35 C. Refrigeration did not have an adverse effect on resistance to irradiation. The presence of water at the time of initial preparation increased this resistance to 0.23 to 0.25 Mrad. Proper drying is essential to achieve reproducible results in sterility tests using USP-type biological indicators.